Alih Aksara dan Alih Bahasa Manuskrip Sejarah Ringkas Syekh Paseban Assyathari Rahimahullah Taala Anhu Disusun Oleh Haji Imam Maulana Abdul Manaf Aminul Khatib - Putri, Delsa Jelita; Nurizzati (Persona: Kajian Bahasa dan Sastra, 2024)
This article aims to: (a) present a manuscript description of the Concise History of Sheikh Paseban Assyathari Rohimahullah Ta’ala ‘‘Anhu. Compiled by Haji Imam Maulana Abdul Manaf Aminul Khotib, (b) present the script translation of the text of the Concise History of Sheikh Paseban Assyathari Rohimahullah Ta’ala ‘‘Anhu. Compiled by Haji Imam Maulana Abdul Manaf Aminul Khotib, (c) presents the translation of the text of the Concise History of Sheikh Paseban Assyathari Rohimahullah Ta’ala ‘Anhu. Compiled by Haji Imam Maulana Abdul Manaf Aminul Khotib. This research is a philological study focused on the manuscript of Brief History of Sheikh Paseban Assyathari Rohimahullah Ta’ala ‘‘Anhu Compiled by Haji Imam Maulana Abdul Manaf Aminul Khotib. The method applied in this research is the philological method which involves several steps. The initial step involves data collection through library research, followed by a detailed description of the manuscript using the descriptive method. Next, transliteration of the manuscript using the transliteration method was conducted, and the final step was translation using the translation method. The results of this study include: (1) a detailed description of the manuscript of Brief History of Sheikh Paseban Assyathari Rohimahullah Ta’ala ‘Anhu Compiled by Haji Imam Maulana Abdul Manaf Aminul Khotib which consists of 18 aspects, (2) transliteration of the text of Brief History of Sheikh Paseban Assyathari Rohimahullah Ta’ala ‘Anhu Compiled by Haji Imam Maulana Abdul Manaf Aminul Khotib from aksar, (3) language transfer of the text of Brief History of Sheikh Paseban Assyathari Rohimahullah Ta'ala ‘Anhu Compiled by Haji Imam Maulana Abdul Manaf Aminul Khotib from Malay and some Minangkabau vocabulary into Indonesian.